Análisis de la configuración de la perspectiva de género en el Ecuador a partir de la entrada en vigencia de la Constitución de la República del Ecuador del 2008 para la elaboración de las políticas públicas en temas de igualdad establecidas en el Plan Nacional del Buen Vivir 2013-2017 - Villamar García, Karla Gabriela (2018)
Ecuador has lived a context rooted in cultural imaginaries and stereotypes that have led to determine what is proper to be a man and be a woman with different roles. This is why there have been several women's movements that have demanded for an effective enjoy your rights in relation to equal conditions and opportunities. The Constitution of the Republic of Ecuador of 2008 has developed advances in its provisions regarding the gender perspective trying to include principles of equality, inclusion and cohesion eradicating discrimination from all areas not only of women but of all social subjects. To verify this it has been decided to compare the Constitution of 2008 with the Political Constitution of 1998. In turn, the intention of this research is to determine whether the principles established in the 2008 order have been the elements that have helped create and mainstream plans and public policies and allowing effective compliance. The normative design that the country now presents through principles of equality and inclusion and good living has given the possibility of building development plans that incorporate the gender approach in their policies to achieve equality between women and men through specialized mechanisms that provide support to disadvantaged groups. As an example of this, Objective 2 of the Plan del Buen Vivir 2013-2017 has been analyzed, which tries to turn Ecuador into a more productive country in economic, social and cultural issues, overcoming the inequality gaps and building equal paths with a methodology that mainstream the gender approach and transform its policies into an effective and real practice. However, it is important to finally point out whether this progress translates into a real and effective practice since, even though the levels of gender discrimination have decreased compared to previous years, these still apply.